Risk perception as a function of age - a psychological investigation - Lang, Britta (Trinity College (Dublin, Ireland). School of Psychology, 2015)
This thesis explored how older drivers' perception of risk differs from that of younger age groups. Its aim was to enhance knowledge that can inform the development of measures to maintain the driving safety of older drivers for as long as possible.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin